Prognostic analysis and clinical and nutritional characteristics of critical Covid-19 patients - Soligo Rovani, Samyra; Puntel, Kaio Luís; Ambrozim de Oliveira, Larissa; Vieira, Ana Paula (Revista Faz Ciência, 2023)
The Covid-19 pandemic represented a challenge for health systems, in large part due to the high mortality rate of the disease in older population, multiform clinical manifestations and prognosis related to nutritional diagnosis and biochemical profile of patients. Objective: to correlate Covid-19 patients admitted to an Intensive Care Unit (ICU) with laboratory tests, anthropometric data and the clinical outcome of the disease. Methodology: an epidemiological and cross-sectional study was performed using secondary databases, analyzing the laboratory (hemoglobin, hematocrit, leukocytes, rods, platelets, creatinine, d-dimer, oxaloacetic transaminase, pyruvic transaminase and C-reactive protein) and nutritional (upper arm circumference, calf circumference and body mass index) parameters of Covid-19 patients admitted to the ICU between March 2020 and March 2021. Sociodemographic, laboratory and clinical data were collected from hospitalized Covid-19 patients in the hospital. Results: inverse correlations were observed between age and anthropometric indicators. The use of a greater number of medications (average 2.1) was associated with lower final Body Mass Index (average 29.2 kg/m²) and arm circumference (average 32.3 cm) values. Patients who died were older, had shorter hospital stays, higher creatinine levels and lower baseline anthropometric indicators. Conclusions: older patients had lower anthropometric values. Patients with chronic diseases had a worse prognosis in the evolution of Covid-19.